Hubungan Asupan Protein Dengan Kadar Ureum, Kreatinin, dan Kadar Hemoglobin Darah pada Penderita Gagal Ginjal Kronik Hemodialisa Rawat Jalan Di RS Tugurejo Semarang - Nura Ma’shumah; Sufiati Bintanah; Erma Handarsari (Universitas Muhammadiyah Semarang, 2014)
Chronic renal failure or end-stage renal disease is a progressive destruction of kidney structure and continuously. Renal function that can not be recovered where the body's ability to maintain metabolic balance, and fluid electrolyte failure, which led to uremia (Elizabeth, 2009). The purpose of this study was to determine the